1992
DOI: 10.1111/j.1365-2869.1992.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscle nerve sympathetic activity during sleep and its change with arousal response

Abstract: Muscle nerve sympathetic activity (MSA) was recorded from the peroneal nerve during wakefulness and in different sleep states in healthy young adults. The burst rate (BR) of MSA significantly decreased in NREM, but not in REM sleep, compared with that during wakefulness. Transient increases of MSA frequently appeared in association with rapid eye movements during REM sleep. K-complexes in Stage 2 were almost always accompanied by a burst of MSA, and were followed by a transient elevation of arterial blood pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
2
23
0
2
Order By: Relevance
“…Increased muscle SNA and BP coincided with the phasic eye movements of REM sleep [10,51], while muscle SNA tended to decrease as REM sleep duration increased [51]. Auditory stimuli causing arousals during NREM sleep also gave rise to a transient increase in muscle SNA and BP [10,51]. It should be emphasized that muscle SNA, although physiologically important, is only part of total SNA.…”
Section: The Cardiovascular System In Normal Sleepmentioning
confidence: 91%
See 2 more Smart Citations
“…Increased muscle SNA and BP coincided with the phasic eye movements of REM sleep [10,51], while muscle SNA tended to decrease as REM sleep duration increased [51]. Auditory stimuli causing arousals during NREM sleep also gave rise to a transient increase in muscle SNA and BP [10,51]. It should be emphasized that muscle SNA, although physiologically important, is only part of total SNA.…”
Section: The Cardiovascular System In Normal Sleepmentioning
confidence: 91%
“…Recent studies in humans have shown that muscle SNA increased above the wakefulness level during tonic REM sleep [42,49], and fell whenever muscle tone increased (REM twitches), concomitant with an increase in BP [42]. Increased muscle SNA and BP coincided with the phasic eye movements of REM sleep [10,51], while muscle SNA tended to decrease as REM sleep duration increased [51]. Auditory stimuli causing arousals during NREM sleep also gave rise to a transient increase in muscle SNA and BP [10,51].…”
Section: The Cardiovascular System In Normal Sleepmentioning
confidence: 99%
See 1 more Smart Citation
“…The sympathetic activity during tonic REM sleep is much higher than that in wakefulness. As differentiated from REM sleep, NREM sleep is characterized by the prevalence of parasympathetic influences [17][18][19].…”
Section: Importance Of Monitoring Of Emotional Stress and Physiologicalmentioning
confidence: 99%
“…28 Arousal from sleep defends against asphyxia but elicits a further, centrallyinitiated increase in sympathetic nerve firing and withdrawal of vagal tone. 29 The oscillations in ventilation characteristic of CSA are accompanied by similar autonomic and chemical disturbances but by less variation in intrathoracic pressure. 30, 31 Hence stroke volume tends to rise subtly rather than fall with each central apnea or hypopnea.…”
Section: Observational Studiesmentioning
confidence: 99%